IMPLEMENTASI PENDIDIKAN KARAKTER RELIGIUS ANAK USIA DINI - Evi Zulianti; Mohammad Afifulloh; Mutiara Sari Dewi (Jurnal Dewantara, 2020)
Religious character education that is applied to early childhood becomes very important because at this age the child's brain will record everything they see or hear from the surrounding environment. These religious habits will become a strong foundation for the child's mental development in the future. Rapid technological advances have positive and negative impacts on children's mental development. Moral decline that is now happening among adults, adolescents and children is our common concern as educators. Religious character education will be the basic solution to instill moral character for children. Because what happens nowadays children will determine their personality in the future. This early childhood religious character education includes positive habits that are carried out daily from activities from waking up to going to sleep again, including habituation of children at school such as giving and answering greetings, sharing, accustomed to praying before and after activities and others etc., but the research was only conducted at school hours by using descriptive qualitative research methods using a case study approach.